The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/1368282021000007749
|View full text |Cite
|
Sign up to set email alerts
|

Cultural variations in attention regulation: A comparative analysis of British and Chinese‐immigrant populations

Abstract: Recent intervention for young children has included parent training. The premise for this training is based in research on parent-child interaction. However, these studies have focused on white, middle-class families. More recent research suggests that not all cultures follow the same pattern. This study explored the relationship between attention regulation, pragmatic input, object manipulation and later language competence in Chinese-immigrant and British caregiver-infant dyads. Microanalytical techniques we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
5
22
0
Order By: Relevance
“…A few studies on the interaction between Malaysian mothers and their adolescent children (Elias & Tan 2009;Keshavarz & Baharudin 2009;Lin & Lian 2011) revealed that Malaysian mothers tend to have expectations that their adolescent children follow their directives either unconditionally (i.e., authoritarian) or with rooms for explanations and negotiations (i.e., authoritative). The findings of culture-specific language teaching beliefs in Malaysia are consistent with findings pertaining to other collectivist cultures, such as those on the Chinese (Johnston & Wong 2002) and Indian mothers (Simmons & Johnston 2007) in Canada, and Chinese mothers in the UK (Vigil 2002). The mothers of these studies demonstrated (1) culture-specific preferences such as the use of instructions over play to teach young children language and (2) more attention-directing behaviours than attention sharing with their young children.…”
Section: General Beliefs On Language Teaching and Learning In Malaysiasupporting
confidence: 79%
“…A few studies on the interaction between Malaysian mothers and their adolescent children (Elias & Tan 2009;Keshavarz & Baharudin 2009;Lin & Lian 2011) revealed that Malaysian mothers tend to have expectations that their adolescent children follow their directives either unconditionally (i.e., authoritarian) or with rooms for explanations and negotiations (i.e., authoritative). The findings of culture-specific language teaching beliefs in Malaysia are consistent with findings pertaining to other collectivist cultures, such as those on the Chinese (Johnston & Wong 2002) and Indian mothers (Simmons & Johnston 2007) in Canada, and Chinese mothers in the UK (Vigil 2002). The mothers of these studies demonstrated (1) culture-specific preferences such as the use of instructions over play to teach young children language and (2) more attention-directing behaviours than attention sharing with their young children.…”
Section: General Beliefs On Language Teaching and Learning In Malaysiasupporting
confidence: 79%
“…Culturally determined definitions of developmental abilities such as knowledge (Zambrano & Greenfield, 2004), creativity (Baldwin, 2001), and language (McCollum & Chen, 2001;Posada, Carbonell, Alzate, & Plata, 2004;Suizzo, 2004;Vigil, 2002) may also affect the ways children and families from linguistically and culturally diverse backgrounds report information. Zambrano and Greenfield (2004) hypothesized that ''different ethnic groups have their own implicit, informal theories of knowledge and that these ethno-theories form the assumptions on which the explicit formal theories are based'' (p. 251).…”
Section: Cultural Equivalencementioning
confidence: 99%
“…Children consistently take roles in ongoing interactions and events in their communities, thus appropriating key-elements from their cultures through joint-exploration (Rogoff, 1990). The current study broadens the scope of accumulated knowledge in the field which established that these processes occur at the microsystem level (Mundy and Neal, 2000; Van-Hecke et al, 2007; Mundy and Jarrold, 2010) and the macrosystem level (Vigil, 2002; Vigil et al, 2006). The present findings extend this line to intermediate levels as well, showing that JA might be the mechanism connecting between cultural values and their behavioral manifestations at various ecological levels.…”
Section: Discussionmentioning
confidence: 74%
“…For example, differences were found between Western and Non-Western societies in JA behaviors. Thus it was shown, that in western societies JA seems to be directed more by the child, as opposed to non-western societies in which JA is more parent-directed (Vigil, 2002). This phenomenon was explained by the different belief systems between the Chinese culture and the British culture regarding the child's abilities and needs (Vigil, 2002).…”
Section: Introductionmentioning
confidence: 99%